Association between body shaming and body image in nursing students: implications for health education from Indonesia - Sari, Citra Windani Mambang; Dewi, Rizky Chintya; Hendrawati, Hendrawati (International Journal of Public Health Science (IJPHS), 2025)
During emerging adulthood, the difference between the ideal body standard and one’s actual body often leads to body-shaming treatment. Persistent experiences of body shaming can significantly harm an individual’s body image. This study aims to identify the association between body-shaming acts and body image in university students. The study population consisted of students aged 18-25 who had experienced body shaming (n = 841). Using a non-probability total sampling method, 448 respondents were included. Data were collected using a body-shaming acts questionnaire and the MBSRQ-AS questionnaire, then analyzed with univariate and bivariate analysis employing the Chi-square test. The results showed a significant relationship between body-shaming acts and body image. Most students received body-shaming treatment at a low level (50.9%), while most body image categories were negative (50.9%). These findings highlight the importance of health workers’ involvement in preventing body-shaming acts and improving students’ body image.